Ioannis Chrysospathis, Theodoros Garofalidis and Georgios Hartofilakidis: the Pioneers of Orthopaedics in Greece - Drakoulakis, Emmanouil; Michaleas, Spyros; Laios, Konstantinos; Lampropoulou-Adamidou, Kalliopi; Tosounidis, Theodoros H; Kontakis, George; Karamanou, Marianna (Scripta Medica, 2024)
The aim of the present paper was to highlight the work of Chrysospathis, Garofalidis and Chartofylakidis, who dedicated themselves to the emergence of orthopaedics as an independent branch of medical science in modern Greece. The ancient Greek physicians Hippocrates, Galen and Paulus of Aegina laid the foundations for the emergence of orthopaedics and ancient Greek civilisation undoubtedly played a significant role in the evolution of this medical art throughout the following centuries. In modern Greece, Ioannis Chrysospathis fought for orthopaedics to be a separate medical branch rather than a practice within the context of general surgery. Theodoros Garofalidis also contributed to the evolution of orthopaedics in Greece, while Georgios Hartofilakidis brought pioneer knowledge to the Greek area, contributed to the creation of specialised orthopaedic departments and internationally contributed to the study of hip diseases and the art of total hip arthroplasty.
Keywords: Ortoped; Hirurgija; Odeljenje za ortopediju; Univerzitet u Atini; Istorija medicine